Recent Developments in Active Metamaterials and their Practical Applications - Tamara Z. Fadhil; Ameer A. Kareim Al-Sahlawi (Al-Iraqia Journal for Scientific Engineering Research)
Mechanical metamaterials are specially designed materials that exhibit unconventional mechanical properties due to their precisely designed microarchitectures and inherent material characteristics. Recent developments have made it possible to create active, tunable, and reconfigurable metamaterials, which provide dynamic control over electromagnetic behavior and offer significant advantages over conventional static systems. In this paper, tuning mechanisms such as circuit-based, geometric, material-driven, and active control mechanisms are comprehensively discussed. It extends to their application in a number of devices, including antennas, filters, imaging devices, and sensors. Although these technologies have a great deal of promise, challenges exist, specifically with respect to fabrication complexity and limited tunability. Continuous breakthroughs in materials science and device engineering will be essential to developing these metamaterials from concepts in the lab to practical, real-world applications. The main contribution of this review is to give a systematic overview of the most recent tuning mechanisms for active metamaterials, while also highlighting the integration of artificial intelligence as a transformative approach for future design and optimization.